Quality of life among breast cancer patients undergoing chemotherapy in Oncology Unit at Hospital Universiti Sains Malaysia - Azman, Wan Nur Atirah Wan (Universiti Sains Malaysia, 2013)
Breast cancer is among the top cancer in women with chemotherapy as an important treatment in curing it. But, the side effects of chemotherapy are always suffered by most cancer patients that could reduce the quality of life (QOL). The goal of this quantitative cross-sectional study was to evaluate the QOL of breast cancer patients undergoing chemotherapy in Oncology Unit at Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan. This study also determine the most common side effects for breast cancer patients undergoing chemotherapy, the level of QOL of breast cancer patients undergoing chemotherapy and to identify the relationship between the domains of QOL (physical, mental and social) with the most common side effects among breast cancer patients undergoing chemotherapy. A total of 52 breast cancer patients were involved using non probability purposive sampling. Data were collected using a self- administered questionnaire which was the Bahasa Malaysia modified version of The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 (EORTC QLQ-C30) version 3.0. The data were gathered and analyzed using SPSS version 20 for frequency, percentage, mean, standard deviation and p-value. Majority of the breast cancer experienced alopecia (mean = 3.75, SD = 0.556), fatigue (mean = 3.65, SD = 0.653) and appetite alteration (mean = 3.62, SD = 0.599) during chemotherapy. Overall, the level of QOL for majority of breast cancer patients undergoing chemotherapy at Hospital USM was at satisfactory level (78.8%). The study found that, there was a significant relationship between social domain and alopecia (r = 0.309, p = 0.026), social domain and fatigue (r = 0.280, p = 0.045) and as well as physical domain and appetite alteration (r = 0.422, p = 0.002). Besides, there was no significant relationship between physical and mental domains on alopecia, physical and mental domains on fatigue and mental and social domains on appetite alteration (p value > 0.05). Since there are negative effects of breast cancer and chemotherapy on patients’ QOL, health care providers, especially nurses, should support the patients throughout their illness and chemotherapy.